Idiopathic Pulmonary Fibrosis Treatment Update 2017
DOI: 10.1136/thoraxjnl-2017-210983.456
|View full text |Cite
|
Sign up to set email alerts
|

M34 Cardiovascular safety of nintedanib in subgroups by cardiovascular risk at baseline in the tomorrow and inpulsis trials

Abstract: Introduction and AimNintedanib is a tyrosine kinase inhibitor, a drug class that may be associated with increased risk of arterial thromboembolic events. The efficacy and safety of 52 weeks’ treatment with nintedanib versus placebo in patients with IPF were assessed in the TOMORROW and INPULSIS trials. Patients with myocardial infarction in the previous 6 months, unstable angina in the previous month, or stroke in the previous year were excluded. We assessed the effect of CV risk at baseline on the CV safety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For major adverse cardiac events including stroke, there was no difference between the intervention and placebo groups, irrespective of baseline risk. The actual clinical significance of these findings is not clear and a notable limitation of this analysis was the size of the lower cardiovascular risk groups (nintedanib: n = 67, placebo: n = 57) in comparison to the higher cardiovascular risk groups (nintedanib: n = 656, placebo: n = 451) [32]. This was due to the fact that 90% of the trial participants had at least 1 risk factor and were classified as higher risk at baseline.…”
Section: Nintedanib Use In Patients With Additional Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For major adverse cardiac events including stroke, there was no difference between the intervention and placebo groups, irrespective of baseline risk. The actual clinical significance of these findings is not clear and a notable limitation of this analysis was the size of the lower cardiovascular risk groups (nintedanib: n = 67, placebo: n = 57) in comparison to the higher cardiovascular risk groups (nintedanib: n = 656, placebo: n = 451) [32]. This was due to the fact that 90% of the trial participants had at least 1 risk factor and were classified as higher risk at baseline.…”
Section: Nintedanib Use In Patients With Additional Risk Factorsmentioning
confidence: 99%
“…To address these findings in greater detail, a retrospective post hoc analysis was performed on the pooled data from the TOMORROW and INPULSIS trials. Data were stratified by intervention and the analysis looked at the incidence of cardiac AEs in those patients considered to be either at higher cardiovascular risk (those with a history of atherosclerotic heart disease or ≥1 cardiovascular risk factor) or at lower cardiovascular risk (no history of atherosclerotic heart disease with no cardiovascular risk factors) at baseline [32]. Here, the incidence of MI was slightly higher in the higher cardiovascular risk intervention group (3.03 per 100 patient years) when compared to the corresponding placebo group (1.16 per 100 patient years).…”
Section: Nintedanib Use In Patients With Additional Risk Factorsmentioning
confidence: 99%
“…Since we observed a reduction in cardiac hypertrophy in NTB treated animals, we were interested in determining if NTB directly affects cardiomyocytes apart from its well- Noth et al investigated the cardiovascular safety of NTB in IPF patients. 23 They perormed an analysis using pooled data from the TOMORROW and INPULSIS trials and concluded that irrespective of cardiovascular risk at baseline, the incidence of major adverse cardiac events was similar between patients treated with NTB vs placebo.…”
Section: Discussionmentioning
confidence: 99%